Towards Random Elixir Code Generation - Facchi, Bernardo Beltrame; Braga, Andrei de Almeida Sampaio; Du Bois, André Rauber; Feitosa, Samuel da Silva (Anais do Simpósio Brasileiro de Linguagens de Programação (SBLP), 2024)
Developers expect compilers to be correct. Unfortunately, these tools are not entirely bug-free. A failure introduced by the compiler could compromise a critical system and consequently have catastrophic consequences, specially in applications of great complexity, affecting both end users and developers. Such failures can lead to significant financial losses, security vulnerabilities, and a loss of trust in the software’s reliability. Therefore, testing and validating all the compiler functionalities to assure its correctness is essential given their importance in software development. In light of the given context, this paper describes a random code generation tool using Haskell that generates well-typed Elixir code by adhering to a specified syntax and typing rules, which serves as input for property-based tests, striving to contribute to the overall quality and dependability of software systems built using Elixir.